RWC Update: Management of Persistent Peripheral Avascular Retina in Retinopathy of Prematurity Survivors; Giant Macular Hole Leading to a Total Retinal Detachment; Proliferative Sickle Cell Retinopathy: Intraoperative Fluorescein Angiography Guided Management - Sharma, Ashish; Wu, Lihteh; Bloom, Steven; Stanga, Paulo; Hartnett, M. Elizabeth; Özdek, Şengül; Vinekar, Anand; Lepore, Domenico; Lepore, Francesca; Temkar, Anand; Nagpal, Manish; Martínez, Eduardo; et al. (Ophthalmic surgery, lasers & imaging, 2025)
Hot Topic in the World of Retina Management of Persistent Peripheral Avascular Retina in Retinopathy of Prematurity Survivors Submitted by: M. Elizabeth Hartnett, MD, FACS; Şengül Özdek, MD, FEBO, FASRS; Anand Vinekar, MS, PhD, FRCS; Domenico Lepore, MD; Francesca Lepore, BS Peripheral persistent avascular retina (PPAR) is very common following regression of retinopathy of prematurity (ROP) either spontaneously or with anti-vascular endothelial growth factor (anti-VEGF) treatment.1,2 There is an ongoing debate about the management of PAR—whether it should be left alone or should be treated with laser photocoagulation (LPC). Socioeconomic factors, particularly in low-resource settings within low- and middle-income countries, further impede consistent follow-up.3 The KIDROP program, currently operational across 177 neonatal units in Karnataka, India, employs a tele-ROP model to mitigate these challenges. In centers with GA or in-patient facilities, follow-up may extend until 55–60 weeks PMA before laser treatment is performed under GA. Late prophylactic laser is considered by many experts worldwide when PAR persists beyond 60 weeks PMA, to avoid exhausting the families' capacity for long-term follow-up.